2021
DOI: 10.3390/su131910865
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Consumer Attitude toward Green Credit Card Services? A Moderated Mediation Approach

Abstract: The purpose of this research is to examine the factors affecting consumer attitude within the context of green credit card services. Specifically, this research examines (1) the effect of individual characteristics (i.e., green knowledge, innovativeness) on attitude toward green credit card services; and (2) the mediating role of self-accountability and the moderating role of regulatory focus in the relationships. With a sample of 1000 green credit/debit card users, structural equation modelling and moderated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The TRI has also been found to have meaningful relationships with the adoption of cryptocurrency Alharbi & Sohaib (2021) [4] and to affect customer perceived value [36]. This scale, especially technology readiness, is one of the scales that is accepted in the evaluation of new technologies by consumers and on which many studies have been conducted in the literature [37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Technological Readiness Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRI has also been found to have meaningful relationships with the adoption of cryptocurrency Alharbi & Sohaib (2021) [4] and to affect customer perceived value [36]. This scale, especially technology readiness, is one of the scales that is accepted in the evaluation of new technologies by consumers and on which many studies have been conducted in the literature [37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Technological Readiness Indexmentioning
confidence: 99%
“…Additionally, consumer innovativeness was found to mediate the relationship between other factors and attitude. For example, Kim and Son (2021) [39] found that innovativeness had a positive effect on attitude, and selfresponsibility mediated the relationship between ecological knowledge and innovativeness and attitude. Shams et al (2020) [90] found that consumer-perceived brand innovativeness and consumer-perceived product innovativeness mediate the effect of brand attitude.…”
Section: The Effect Of Innovativeness On Attitude Towards Usagementioning
confidence: 99%